2019
DOI: 10.1016/j.combustflame.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of kinetics on DDT simulations

Abstract: Deflagration to Detonation Transition (DDT) is an intricate problem that has been tackled numerically, until recently, using single-step chemical schemes. These studies (summarized in Oran and Gamezo, 2007) [1] showed that DDT is triggered when a gradient of reactivity forms inside a pocket of unreacted material. However, recent numerical simulations of hydrogen/air explosions using detailed reaction mechanisms (Liberman et al., 2010; Ivanov et al., 2011) [2,3] showed that detonation waves can emerge from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Numerical simulation results were obtained using identical mathematical models and source data (Figs. [15][16][17][18][19][20]. The form and orientation of the isosurface resembles that for design variant 1, though with smaller deformation of the base.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Numerical simulation results were obtained using identical mathematical models and source data (Figs. [15][16][17][18][19][20]. The form and orientation of the isosurface resembles that for design variant 1, though with smaller deformation of the base.…”
Section: Discussionmentioning
confidence: 87%
“…Paper [20] examined chemical modelling and its influence on the transition of combustion conditions from deflagration to detonation. It was shown that, in the case of hydrogen-air mixtures, the multi-step chemical description is far more restrictive than the single-step model when it comes to the necessary conditions for a hot spot to lead to detonation.…”
Section: Introductionmentioning
confidence: 99%
“…[11] using one-step chemistry and by Dounia et al [27] using detailed chemistry. As discussed previously, in all the cases presented in Fig.…”
Section: Detonation Initiation Mechanismmentioning
confidence: 99%
“…While numerical simulations using complex chemistry with detailed chemical reaction rates are nowadays possible with increasing computational resources, it remains challenging to fully synthesize and explain the tremendous amount of chemical kinetic and flow field information that are generated from the computation. In fact, although recent studies have shown that detailed chemical kinetics plays an important role in detonation dynamics and its use may introduce additional transient and multiscale effects [52][53][54][55], qualitative comparison with simulations using a detailed reaction mechanism has shown the simplified chemistry models, e.g., one-step or two-step chain-branching type kinetics, correctly elucidate the underlying physics of the ODW dynamics, importantly the two transition processes this study is focusing on, e.g., References [38,39,56]. In addition, the two-step induction-reaction kinetics, consisting of a thermally neutral induction step followed by a main heat release reaction layer, provides a compromise on the detailed chemistry model.…”
Section: Introductionmentioning
confidence: 99%